EFEK PROTEIN SEMPURNA DAN TIDAK SEMPURNA TERHADAP BERAT BADAN DAN ALBUMIN TIKUS - Hermawati, hermawati; Salam, Abdul; Manti Battung, Sabaria (Jurnal Gizi Masyarakat Indonesia (The Journal of Indonesian Community Nutrition), 2019)
Introduction: Protein is the trigger for the occurrence of obesity and changes in albumin levels in weight gain. Obesity is one of the most serious public health challenges in the 21st century. Objektive: This study aimed to determine the effects of high-protein complete and uncomplete diet to weight gain and albumin levels in wistar rats. Methods: The samples used 15 wistas rats which were divided randomly into 3 groups, each consisting of 5 tails weighing 150-200 g and in healthy condition. Standard AD 2 feed was given to the control group, intervention feed given to complete protein and soybean intervention feed protein group was uncomplete. The study was conducted for 6 weeks, 2 weeks of adaptation and 4 weeks of intervention. The research method used a true experiment with a randomized control group pretest-posttest desigen. The data collected consisted of weighing the body and measuring the rat albumin level which was carried out 2 times before the intervention day 0 and after the intervention of the 28th day. Data analysis used One Way ANOVA statistical test followed by Post Hoc Tukey and Paired Sample Test was accepted if p <0.05. Results: The results of measurements of weight gain obtained before the intervention were not significant with p = 0.790 and measurements after intervention obtained significant results with a value of p = 0.014, as well as examination of insignificant albumin levels before intervention with p = 0.251 and significant on examination after the intervention with a value of p = 0.003. Conclusion: It It can be concluded as an intervention after weight gain and albumin levels.